Comparative Effects of Plant and Animal Liquid Organic Fertilizers on Soil Fertility, Nutrient Uptake, and Shallot Yield in Ultisols - Ansyori, Ansyori; Lamdo, Herfandi; Anissa, Nabillah; Putri, Tika Leoni; Soleha, Soleha; Mar’ah, Dian Latifathul; Fahmi, Putri Mariska (Agro Bali : Agricultural Journal, 2026)
Ultisols are characterized by strong acidity, low cation exchange capacity, and high phosphate fixation, which limit nutrient availability and crop productivity. Sustainable fertilization strategies are needed to improve soil quality and reduce dependence on inorganic inputs. A pot experiment was conducted from January to August 2025 using a randomized complete block design with nine treatments and three replications (270 plants). Treatments included combinations of 50% NPK fertilizer with liquid organic fertilizers (LOFs) derived from goat urine, rabbit urine, banana peels, and pineapple peels. Data were analyzed using analysis of variance (ANOVA), followed by orthogonal comparison tests. The combined application of LOFs with 50% NPK significantly increased biomass, bulb yield, soil CEC, organic C, total N, available K, and plant N and K uptake (p < 0.01) compared to 100% NPK. Yield increased by 27.7%, while N and K uptake rose by 63.0% and 65.0%, respectively. Rabbit urine LOF showed the highest effectiveness, improving yield by up to 36.0% compared to goat urine. Plant-based LOFs enhanced soil organic C, CEC, and K availability, whereas animal-based LOFs were more effective in increasing soil N. The integration of LOFs with reduced NPK improves soil fertility and shallot productivity under controlled conditions. Rabbit urine LOF at 300 mL L⁻¹ is the most effective treatment. However, field validation is required before large-scale application.